The handbook of credit risk management : originating, assessing, and managing credit exposures - Bouteille, Sylvain; Coogan-Pushner, Diane (Hoboken, New Jersey : Wiley, 2013)
Comprehensive guide to credit risk management/b/ i/i/ iThe Handbook of Credit Risk Management/i presents a comprehensive overview of the practice of credit risk management for a large institution. It is a guide for professionals and students wanting a deeper understanding of how to manage credit exposures. The Handbook provides a detailed roadmap for managing beyond the financial analysis of individual transactions and counterparties. Written in a straightforward and accessible style, the authors outline how to manage a portfolio of credit exposures--from origination and assessment of credit fundamentals to hedging and pricing. The Handbook is relevant for corporations, pension funds, endowments, asset managers, banks and insurance companies alike./ ulliCovers the four essential aspects of credit risk management: Origination, Credit Risk Assessment, Portfolio Management and Risk Transfer./liliProvides ample references to and examples of credit market services as a resource for those readers having credit risk responsibilities./liliDesigned for busy professionals as well as finance, risk management and MBA students./li/ul As financial transactions grow more complex, proactive management of credit portfolios is no longer optional for an institution, but a matter of survival. & gt.
Origination. Fundamentals of Credit Risk -- Governance -- Checklist for Origination -- Credit Assessment. Measurement of Credit Risk -- Dynamic Credit Exposure -- Fundamental Credit Analysis -- Alternative Estimations of Credit Quality -- Securitization -- Portfolio Management. Credit Portfolio Management -- Economic Capital and Credit Value at Risk (CVaR) -- Regulation -- Accounting Implications of Credit Risk -- Mitigation and Transfer. Mitigating Derivative Counterparty Credit Risk -- Structural Mitigation -- Credit Insurance, Surety Bonds, and Letters of Credit -- Credit Derivatives -- Collateral Debt Obligations (CDOs) -- Bankruptcy.
Includes index.
Description based on print version record and CIP data provided by publisher.
Keywords: Credit -- Management; Risk management; BUSINESS & ECONOMICS / Finance; Credit -- Management; Risk management; Electronic books; Electronic books